2014
DOI: 10.1177/0961203314540353
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus is an effective treatment for lupus nephritis in pregnancy

Abstract: Lupus nephritis during pregnancy increases morbidity and mortality for mother and baby. Flares are difficult to treat as many therapeutic options are teratogenic or fetotoxic. Steroids alone may be unable to control disease activity and are associated with higher rates of preterm delivery, sepsis and gestational diabetes. Reports of using tacrolimus to treat lupus nephritis in pregnancy are limited. We describe the pregnancies of nine women in whom tacrolimus was successfully used to treat lupus nephritis flar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 21 publications
0
35
0
6
Order By: Relevance
“…Tacrolimus is a calcineurin inhibitor that has been used successfully in both the maintenance of stable disease and treatment of lupus nephritis flare in pregnancy in several case series, in which no adverse outcomes were observed [126,127]. It is considered safe for use in pregnancy [128,129]; the lowest effective dose should be used and levels must be followed to avoid toxicity.…”
Section: Medications During Autoimmune Ctd Pregnanciesmentioning
confidence: 99%
“…Tacrolimus is a calcineurin inhibitor that has been used successfully in both the maintenance of stable disease and treatment of lupus nephritis flare in pregnancy in several case series, in which no adverse outcomes were observed [126,127]. It is considered safe for use in pregnancy [128,129]; the lowest effective dose should be used and levels must be followed to avoid toxicity.…”
Section: Medications During Autoimmune Ctd Pregnanciesmentioning
confidence: 99%
“…Therefore, MMF is contraindicated during pregnancy. On the contrary, TAC is not linked to congenital malformations in solid organ transplantation43 and has been successfully used to treat LN flares during pregnancy 44…”
Section: Discussionmentioning
confidence: 99%
“…MMF is contraindicated during 409 pregnancy due to a link with increased incidence of first-trimester preg- ticipants [37]. Potential problems using tacrolimus may arise from 428 the complex pharmacokinetics, which will be altered in pregnancy, 429 increasing the risk of toxicity due to higher unbound drug fractions.…”
mentioning
confidence: 99%
“…review identified 1 case report, a case series of 2 pa-252 tients, and a retrospective analysis of 9 patients all successfully treated 253 with tacrolimus during pregnancy[35][36][37]. Overall five of these cases254 were already taking tacrolimus prior to pregnancy and had quiescent 255 disease throughout.…”
mentioning
confidence: 99%